Types of COVID-19 clusters and their relationship with social distancing in the Seoul metropolitan area, South Korea. (May 2021) - Choi, Yoon-Jung; Park, Mi-jeong; Park, Soo Jin; Hong, Dongui; Lee, Sohyae; Lee, Kyung-Shin; Moon, Sungji; Cho, Jinwoo; Jang, Yoonyoung; Lee, Dongwook; Shin, Aesun; Hong, Yun-Chul; et al.
Highlights: All the reported COVID-19 clusters were identified and categorized in South Korea. COVID-19 clusters are categorized into large, medium, and small clusters. Cluster distributions are correlated with the government's social distancing measures. Abstract: Background: The complete contact tracing of coronavirus disease-19 (COVID-19) cases in South Korea allows a unique opportunity to investigate cluster characteristics. This study aimed to investigate all reported COVID-19 clusters in the Seoul metropolitan area from January 23 to September 24, 2020. Methods: Publicly available COVID-19 data was collected from the Seoul Metropolitan City and Gyeonggi Province. Community clusters with ≥5 cases were characterized by size and duration, categorized using K-means clustering, and the correlation between the types of clusters and the level of social distancing investigated. Results: A total of 134 clusters comprised of 4033 cases were identified. The clusters were categorized into small (type I and II), medium (type III), and large (type IV) clusters. A comparable number of daily reported cases in different time periods were composed of different types of clusters. Increased social distancing was related to a shift from large to small-sized clusters. Conclusions: Classification of clusters may provide opportunities to understand the pattern of COVID-19 outbreaks better and implement more effective suppression strategies. Social distancing administered by the government may effectively suppress large clusters but may not effectively control small and sporadic clusters.